The private archives and archival materials in the Central and East European countries : materials of the International Conference, Madralin, October 8-11, 1998 - edited by Wladyslaw Stepniak. (Naczelna Dyrekcja Archiwów Panstwowych, 1999)
[Sponsored by] "The General Head Office of State Archives, The Association of Polish Archives [and] State Committee for Scientific Research." Includes bibliographical references.Text in English and Russian with summaries in Russian and English.